Comportamiento de componentes agronómicos y de rendimiento bajo dosis creciente de gallinaza en Capsicum annuum L. “pimiento”, Zungarococha-Loreto. 2021 - Perea Angulo, Karolyn (2022)
The experiment "Behavior of agronomic components and yield under increasing dose of chicken in Capsicum annuum L. "pepper", Zungarococha- Loreto. 2021", was perpetrated in the facilities of the Workshop of Teaching and Research of Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located south of the city of Iquitos, near the Populated Center of Zungarococha, The type of research was experimental, quantitative, explanatory, transversal, prospective with an independent variable (increasing dose of chicken) and eight dependent variables (plant height, plant diameter, fruit length, fruit diameter, number of fruits/plant, fruit weight, fruit weight/plant and fruit weight/ha). the objective of the research work was to determine the behavior of the agronomic and yield components under increasing dose of chicken in Capsicum annuum L. "pepper", Zungarococha-Loreto. The experimental design that was used was the Completely Random Block Design, with four treatments and four repetitions. Each experimental unit consisted of 2 rows, 5 floors/row and the sampling unit consisted of four plants/experimental unit. At the end of the experiment the following conclusions were reached: There are differences in the behavior of the agronomic and yield components according to the increase in the dose of chicken, in the cultivation of Capsicum annuum L. "pepper"; the fertilization of greater influence on the behavior of the agronomic components and yield was 60 t of hen /ha that corresponded to the T4 treatment. The T4 treatment (60 t of chicken /ha), presented the highest yield of weight of fruits / ha, with 38,364 Kg and also obtained the best Benefit / Cost ratio, presenting an economic utility of S / .58,226.00.